If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying k + -3 = 40 Reorder the terms: -3 + k = 40 Solving -3 + k = 40 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + k = 40 + 3 Combine like terms: -3 + 3 = 0 0 + k = 40 + 3 k = 40 + 3 Combine like terms: 40 + 3 = 43 k = 43 Simplifying k = 43
| cos^2x-5sinx+5=0 | | (2x+3.71)31=1136.77 | | (x+3)2=121 | | 109=-3-8r | | 7-7=9x+5x | | W-13.7=2.8 | | 9(3x-6+5y)= | | 3*-2+2=-2-2 | | -14-8x=66 | | 10.50x+18=50 | | 5n-10=n+2 | | 30-2(a+1)=8 | | -8(x+9)-8=-80 | | x^2-13xy+22y^2= | | 3x-12-x= | | 7d-(6-2d)=12 | | 6x^2+7xy-20y^2=0 | | 10y+10=4+4y | | 49-98x+12x^2=0 | | 8y-27=5 | | -20+7x=-28 | | 3a-4=2a+7 | | (x+4)(480s-0.5)-480=0 | | X-.06x=323 | | 6k+2=116 | | 0.50x-0.20(50+x)=0.04(50) | | 41=.5x+(-4) | | 8y=37 | | 5d+99=11d-99 | | at+ap=m | | 5x+10=150 | | 86z-86=49z-49 |